Estimates of the damage caused by the earthquake by using RADIUS and GIS (Case Study city Ashkezar) - Ali Almodaresi; Ahmad Mirdehghan (مخاطرات محیط طبیعی, 2018)
Earthquake is a natural phenomenon that ignoring it causes irreparable damage, therefore seismic vulnerability assessment of residential districts is one of the necessities of urban management. By creating an appropriate model and employing a variety of spatial and non-spatial data and analyzing geographic information and multi-criteria decision-taking systems one can assess and analyze seismic vulnerability of cities against earthquakes. In this study Ashkezar city as one of Yazd province cities is chosen for vulnerability assessment. In this study Radius model is used for vulnerability assessment. This model’s input data is: 1-the size of the district under study 2-district population 3-total number of buildings 4-soil properties 5-vital arteries information 6-earthquake scenario; and its output data is earthquake magnitude, damages on buildings, vital arteries and casualties.The results show that earthquake damages by two possible scenarios in the district under study are very low so that in southwest fault scenario the damage is low and in eastern fault scenario there is no damage.